FROM PANDEMIC SURGE TO POST-CRISIS SLUMP: VALUING HEALTHCARE FIRMS THROUGH FINANCIAL VOLATILITY - Hidayat, Ujang Syaiful (Universitas 17 Agustus 1945 Surabaya, 2025)
The COVID-19 pandemic significantly heightened demand for healthcare services; however, many companies in the sector faced declining revenues and financial instability once the crisis subsided. This study investigates the effects of profit volatility on dividend policy and its subsequent impact on investor valuation for Indonesian healthcare companies from 2020 to 2023, employing a quantitative approach with a descriptive-causal research design. Analyzing financial data from seven IDX-listed healthcare firms using Multi Regression Analysis (MRA) in SmartPLS software reveals that, despite increased income volatility, stable dividends can enhance investor valuation, albeit to a limited extent. Furthermore, a robust Dividend Policy appears to drive higher Investor Valuation more effectively than dividend stability alone. While consistent dividend distributions marginally elevate company valuations among investors, the mediating effect of Dividend Stability is found to be positive yet minimal, indicating a negligible practical impact.